2009
DOI: 10.1111/j.1467-789x.2009.00597.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the hypothalamic pathways and its role on obesity

Abstract: Over recent decades, the prevalence of obesity has increased dramatically worldwide. Although this epidemic is mainly attributable to modern (western) lifestyle, multiple twin and adoption studies indicate the significant role of genes in the individual's predisposition to becoming obese. As the hypothalamus plays a central role in controlling body weight, its regulatory circuits may represent a crucial system in the pathogenesis of the disorder. Genetic variations in genes in the hypothalamic pathways may the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 173 publications
(262 reference statements)
0
19
0
3
Order By: Relevance
“…The 1084 SNPs spanning the 31 selected candidate genes were used to perform the post hoc association analysis for effects of gene-by-drug interactions on weight gain during the course of treatment. Genes related to body weight regulation were selected, in part, because of their roles in the neural systems affected by psychotropic agents and included (Chung and Leibel (, 2008; Lindgren and McCarthy, 2008; van Vliet-Ostaptchouk et al 2009; Walley et al 2009). These included the dopamine receptors DRD2 and DRD4 ; Serotonin Transporter ( SLC6A4 ), 5-Hydroxytryptamine Receptors (HTR1A, HTR2A, HTR2C, HTR1F , and HTR6) ; adrenergic receptors ( ADRA1A, ADRA2A, ADRB3); Histamine receptors 1 and 2 ( HRH1, HRH2 ); Cholinergic receptor, muscarinic 3 ( CHRM3 ); synaptosomal associated protein SNAP25 ; genes associated with obesity including Leptin ( LEP ), Leptin receptor ( LEPR ), and fat mass and obesity associated ( FTO ); and genes associated with type 2 diabetes including peroxisome proliferator activated receptor gamma ( PPARG ); Transcription Factor 7 Like 2 ( TCF7L2 ), Potassium Channel Inwardly Rectifying Subfamily J Member 11( KCNJ11 ), hematopoietically expressed homeobox ( HHEX ), Insulin like Growth Factor Binding Protein 2 ( IGF2BP2 ), CDK5 Regulator Subunit-Associated Protein 1-Like ( CDKAL1 ), Solute carrier family 30 member 8 ( SLC30A8 ), Cyclin Dependent Kinase Inhibitors 2A and 2B ( CDKN2A and CDKN2B ), and Insulin degrading enzyme ( IDE ).…”
Section: Methodsmentioning
confidence: 99%
“…The 1084 SNPs spanning the 31 selected candidate genes were used to perform the post hoc association analysis for effects of gene-by-drug interactions on weight gain during the course of treatment. Genes related to body weight regulation were selected, in part, because of their roles in the neural systems affected by psychotropic agents and included (Chung and Leibel (, 2008; Lindgren and McCarthy, 2008; van Vliet-Ostaptchouk et al 2009; Walley et al 2009). These included the dopamine receptors DRD2 and DRD4 ; Serotonin Transporter ( SLC6A4 ), 5-Hydroxytryptamine Receptors (HTR1A, HTR2A, HTR2C, HTR1F , and HTR6) ; adrenergic receptors ( ADRA1A, ADRA2A, ADRB3); Histamine receptors 1 and 2 ( HRH1, HRH2 ); Cholinergic receptor, muscarinic 3 ( CHRM3 ); synaptosomal associated protein SNAP25 ; genes associated with obesity including Leptin ( LEP ), Leptin receptor ( LEPR ), and fat mass and obesity associated ( FTO ); and genes associated with type 2 diabetes including peroxisome proliferator activated receptor gamma ( PPARG ); Transcription Factor 7 Like 2 ( TCF7L2 ), Potassium Channel Inwardly Rectifying Subfamily J Member 11( KCNJ11 ), hematopoietically expressed homeobox ( HHEX ), Insulin like Growth Factor Binding Protein 2 ( IGF2BP2 ), CDK5 Regulator Subunit-Associated Protein 1-Like ( CDKAL1 ), Solute carrier family 30 member 8 ( SLC30A8 ), Cyclin Dependent Kinase Inhibitors 2A and 2B ( CDKN2A and CDKN2B ), and Insulin degrading enzyme ( IDE ).…”
Section: Methodsmentioning
confidence: 99%
“…1). 7 - 12 This small region of the brain coordinates the nervous and endocrine systems to regulate energy balance and other homeostatic activities 13 . Both rare mutations and common variants have been found in genes encoding proteins that are involved in the neural responses to leptin, a key hormone produced by adipose tissue.…”
mentioning
confidence: 99%
“…The majority of the genes, in which mutations cause monogenic obesity, are involved in the control of appetite and food intake through the hypothalamus [28]. Similarly, most of the 24 loci analysed in the present study are suggested to include genes with hypothalamic expression, although the specific molecular mechanisms behind these links are not well characterised [28].…”
Section: Discussionmentioning
confidence: 79%